Translation and interpreting in the 20th century : focus on German - Wilss, Wolfram (Benjamins translation library, 1999)
This book provides a historical survey of the unfolding of translation and interpreting (language mediation) in the 20th century with special reference to the German-speaking area. It is based first, on extensive archive research in Austria, Germany, and Switzerland, second, on a large number of interviews with experts in the field of language mediation, and third, on the author's observations and experiences in the field of translation practice, translation teaching, and translation studies between 1950-1995. A specific feature of the book is the description of the social role of the language.